Pengaruh Penempatan Kerja Dan Beban Kerja Terhadap Kinerja Pegawai Satuan Polisi Pamong Praja Dan Pemadam Kebakaran Kabupaten Sikka - Agustina Dua Ona; Imanuel Wellem; Yosef Tonce (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2024)
This study aimed to (1) understand the overwiew of Employee Performance, Job Placement, and Workload; and (2) analyze the influence of job Placement and Workload on Enployee Performance, both partially and simultaneously. The population of this study consisted of employes of the Civil Service Police Unit and Fire Departement of Sikka Regency. Due to the limited population, this study was conducted using a census or sampling method , with 48 samples determined using Slovin’s formula. Data were collected through questionnaires and analyzed using descriptive and inferential statistical methods, specifically multiple linear regression. Hypothesis testing was conducted F-tests and t-tests. The descriptive analysis results indicated that the Employee Performance variable was categorized as good, the job Placement variable was categorized as good, and the Workload variable was categorized as low. The t-test results showed that, partially, the job Placement variable had a positive but insignificant effect on Employee Performancee. Meanwhile, the Workload variable had a negative and insignificant effect on Employee Performance. The F-test results showed that, simultaneously, the job Placement and Workload variabels had a significant effect on Empolyee Performance. The coefficient of determination analysis showed that the two independent variabels in this study explained 15,3% of the variation in Empolyee Performance at the Civil Service Police Unit and Fire Depertement of Sikka Regency